2007
DOI: 10.1128/aac.00277-07
|View full text |Cite
|
Sign up to set email alerts
|

Activity against Human Immunodeficiency Virus Type 1, Intracellular Metabolism, and Effects on Human DNA Polymerases of 4′-Ethynyl-2-Fluoro-2′-Deoxyadenosine

Abstract: We examined the intracytoplasmic anabolism and kinetics of antiviral activity against human immunodeficiency virus type 1 (HIV-1) of a nucleoside reverse transcriptase inhibitor, 4-ethynyl-2-fluoro-2-deoxyadenosine (EFdA), which has potent activity against wild-type and multidrug-resistant HIV-1 strains. When CEM cells were exposed to 0.1 M

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 26 publications
4
107
0
2
Order By: Relevance
“…We propose this is due to improved binding and catalytic incorporation into the viral DNA (Fig. 4B); also, the 3′-OH of EFdA contributes to its rapid and facile activation by the deoxycytidine kinase (6,18). Finally, regarding 2-F, it contributes to improved inhibitor binding at the polymerase active site (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…We propose this is due to improved binding and catalytic incorporation into the viral DNA (Fig. 4B); also, the 3′-OH of EFdA contributes to its rapid and facile activation by the deoxycytidine kinase (6,18). Finally, regarding 2-F, it contributes to improved inhibitor binding at the polymerase active site (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The lack of a 3Ј-OH on current clinically used NRTIs can reduce recognition by cellular nucleoside/nucleotide kinases that have evolved to interact with the 3Ј-OH present in their natural nucleoside substrates (9). Preliminary studies suggest that EFdA appears to undergo rapid and facile intracellular conversion to the active antiviral EFdA-TP (36), showing that the 4Ј-ethynyl group does not interfere with recognition by cellular nucleoside/nucleotide kinases. Furthermore, the presence of fluorine at position 2 of the adenine base of EFdA helps to stabilize intracellular levels of EFdA and its phosphorylated products by hindering adenosine deaminasecatalyzed degradation of the molecule (13).…”
Section: Discussionmentioning
confidence: 99%
“…EFdA and ECldA showed very high activity against all HIVs and acceptable SIs, however, the activity of ECldA is lower than that of EFdA. These results indicated that the 3'-OH played important roles not only for the phosphorylation of 5'-OH, but also for the activity against drug-resistant HIVs [34].…”
Section: Intravenous Administrationmentioning
confidence: 88%